The Effect of the Context of Science, Pseudoscience Demarcation on the Science Perceptions of Secondary School Students: The Case of Iridology - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2015)
The current study investigating the effect of a process planned in the context of science and pseudoscience demarcation on the development of science perception of secondary school students was designed upon an iridology case. In the process of the research, iridology was first presented to the students, sample applications were made and discussed in the class in general sense. Following that, the case was taken in detail with the small groups formed in the class and ended with the reports of group discussions. The data sources of the research of which participants were 21 secondary school students was comprised of The Form for Science, Pseudoscience Demarcation (FSPD) and group discussion reports and the data obtained was analysed qualitatively. The results of the study revealed that beliefs about science can be elicited and substantially developed in the context of demarcation of science from pseudoscience. It was found that participants had continued to accept empirical inquiry as a criterion of being scientific whereas reduced their emphasis on authority's point of views. After intervention some of them had also mentioned consistency and acceptance by community of science as new criteria for being scientific.
Keywords: Nature of science; Pseudoscience; Perception of Science; Iridology; ELEMENTARY TEACHERS CONCEPTIONS; IDEAS-ABOUT-SCIENCE; VIEWS; INQUIRY